2015
DOI: 10.1016/j.apergo.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in predicted survival times in cold water due to wind and waves

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…These discrepancies were the justification for our recent experimental investigation of the effects of wind and waves on predicted survival times (Power et al, 2015). We confirmed that immersions in wind and waves will significantly increase heat loss compared to calm water, and that predicted survival time is reduced as a consequence, which is exacerbated as water temperature decreases.…”
Section: Introductionsupporting
confidence: 73%
“…These discrepancies were the justification for our recent experimental investigation of the effects of wind and waves on predicted survival times (Power et al, 2015). We confirmed that immersions in wind and waves will significantly increase heat loss compared to calm water, and that predicted survival time is reduced as a consequence, which is exacerbated as water temperature decreases.…”
Section: Introductionsupporting
confidence: 73%
“…Heat loss can occur by conduction of heat from the skin to the cold water around the body. It has been shown that mean skin heat loss was higher in wind and waves [115].…”
Section: The Risk Of Hypothermia In Cold Water Swimmingmentioning
confidence: 99%
“…Deep body temperature regulation is a balancing act between inputs that cool the body (for example cold water, wind and waves 19 ) and those that can increase heat production (exercise and shivering) or maintain heat storage (insulation from clothing, unperfused muscle and body fat). The temperature and duration of immersion endured in 17°C waters is likely to result in a fall in deep body temperature (from approximately 37°C) and may result in hypothermia (a deep body temperature below 35°C, immersion phase three 12 ).…”
Section: Deep Body Coolingmentioning
confidence: 99%